2014
DOI: 10.1111/ijmr.12041
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Political Skill: Current Research Trend and Directions for Future Research

Abstract: This paper reviews theoretical and empirical research on the use of political skill in organizations and proposes some agendas for future research. Although political skill is a relatively new construct in organizational politics research, a large number of theoretical and empirical studies have been conducted. Five major themes were identified in previous research. These are: (a) definition and measurement of political skill; (b) political skill and stress management; (c) political skill and career success; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
138
0
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(158 citation statements)
references
References 161 publications
(305 reference statements)
6
138
0
14
Order By: Relevance
“…Such an assertion is supported by amassing empirical evidence associating political skill with favorable personal and organizational outcomes (e.g., Bing, Davison, Minor, Novicevic, & Frink, 2011;Ferris, Treadway, Brouer, & Munyon, 2012;Kimura, 2015;Munyon, Summers, Thompson, & Ferris, 2015;Wihler, Frieder, Blickle, Oerder, & Schütte, 2016). For example a meta-analysis by Bing et al (2011) showed that a positive relationship between political skill and task performance was present, however, such a relationship applied only to occupations that required intense social influence tactics, based on the categorization of Occupational Information Network (O*NET) developed by the U.S. Department of Labor.…”
Section: Political Skill αS a Quality Assurance Mechanismmentioning
confidence: 99%
See 3 more Smart Citations
“…Such an assertion is supported by amassing empirical evidence associating political skill with favorable personal and organizational outcomes (e.g., Bing, Davison, Minor, Novicevic, & Frink, 2011;Ferris, Treadway, Brouer, & Munyon, 2012;Kimura, 2015;Munyon, Summers, Thompson, & Ferris, 2015;Wihler, Frieder, Blickle, Oerder, & Schütte, 2016). For example a meta-analysis by Bing et al (2011) showed that a positive relationship between political skill and task performance was present, however, such a relationship applied only to occupations that required intense social influence tactics, based on the categorization of Occupational Information Network (O*NET) developed by the U.S. Department of Labor.…”
Section: Political Skill αS a Quality Assurance Mechanismmentioning
confidence: 99%
“…In this respect, political skill helps diagnose those influence tactics that seem relevant to the situation and to the target, while it promotes the self-confidence of the agent in exerting influence and increases the effectiveness of influence attempts (Farmer & Maslyn, 1999;Kolodinsky et al, 2007). Indeed Kimura (2015) suggests that politically skilled employees may fit their behavior to the situation and do so in an authentic manner that reinforces trust, while Wihler et al (2016) note that leaders who are strong in political skill engage in situationally specific behavior (i.e., transformational/relational-oriented or transactional/maintenance-oriented) depending on the needs of multiple stakeholders. Finally, those high on political skill may neutralize stressors (e.g., Perrewé et al, 2004) and help resolve tensions ensued from the use of seemingly antipodal behaviors.…”
Section: The Moderating Role Of Political Skillmentioning
confidence: 99%
See 2 more Smart Citations
“…literature that stems from a lack of theoretical specification regarding political skill's dimensions Kimura, 2015).…”
mentioning
confidence: 99%